2008
DOI: 10.1038/onc.2008.259
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-based treatment of glioblastomas with ABT-737, a novel small molecule inhibitor of Bcl-2 family proteins

Abstract: Defects in the apoptotic signaling cascades contribute to the poor therapeutic response of malignant gliomas. As glioblastomas are characterized by high expression levels of anti-apoptotic Bcl-2 family proteins, we studied the effects of the novel Bcl-2 inhibitor, ABT-737, on malignant glioma cells. ABT-737 treatment released the pro-apoptotic Bax protein from its binding partner Bcl-2 and potently induced apoptotic cell death in glioblastoma cells in vitro and in vivo. The local administration of ABT-737 prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 49 publications
8
159
0
1
Order By: Relevance
“…35,36 We previously reported that siRNA-mediated downregulation of Mcl-1 in glioblastoma cells results in a potent sensitization to ABT-737-induced apoptosis. 37 Similarly, the knockdown of Mcl-1 significantly increased the sensitivity of glioblastoma cells to the death ligand TRAIL (Figure 6c). Accordingly, overexpression of Mcl-1 rescued Notch1-mediated sensitization to ABT-737 and TRAILinduced apoptosis (Supplementary Figure S11) and inhibited cell death caused by Notch1 knockdown (Supplementary Figure S12).…”
Section: Notch1 Inhibition Sensitizes Glioblastoma Cells For Anti-tummentioning
confidence: 80%
See 2 more Smart Citations
“…35,36 We previously reported that siRNA-mediated downregulation of Mcl-1 in glioblastoma cells results in a potent sensitization to ABT-737-induced apoptosis. 37 Similarly, the knockdown of Mcl-1 significantly increased the sensitivity of glioblastoma cells to the death ligand TRAIL (Figure 6c). Accordingly, overexpression of Mcl-1 rescued Notch1-mediated sensitization to ABT-737 and TRAILinduced apoptosis (Supplementary Figure S11) and inhibited cell death caused by Notch1 knockdown (Supplementary Figure S12).…”
Section: Notch1 Inhibition Sensitizes Glioblastoma Cells For Anti-tummentioning
confidence: 80%
“…Synergy was evaluated by the fractional product method that allows an evaluation of synergy at a defined level of effect. 37 Statistical analysis of in vivo survival experiments was performed with the log rank test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,42 As Noxa potently binds to Mcl-1, 6 its ability to promote ABT-737 induction of cell death generally relies on its capacity to inhibit Mcl-1 that is not targeted by ABT-737. [13][14][15][16][17] Silencing of Mcl-1 increased cell death rates in ABT-737-treated U251 cells (without affecting Noxa expression in untreated or ABT-737-treated cells, Supplementary Figures S3A and S3B). This is consistent with the notion that, in these cells, Mcl-1 represents a major restrain to ABT-737 efficiency that Noxa induction contributes to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sensitivity to ABT-737 is enhanced by combined treatments that decrease Mcl-1 expression and/or induce Noxa, a BH3-only protein that essentially functions as an inhibitor of Mcl-1. [13][14][15][16][17][18] ABT-737 is a powerful tool to investigate how death signals induced by direct inhibition of subsets of anti-apoptotic Bcl-2 family members lead to cell demise. Caspase activity contributes to the final stages of cell death induced by inhibition of Bcl-2 homologs.…”
mentioning
confidence: 99%